2007
DOI: 10.1016/s0210-4806(07)73734-8
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la progresión del cáncer de próstata incidental según el tipo de tratamiento aplicado

Abstract: While in low risk patients watchful waiting represents an acceptable aproaching, it could not be adequate in high risk cases. Hormonotherapy showed no benefit in incidental prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The patients that were excluded from the study and did have persistent uptake did not have biopsy nor had their serum PSA evaluated due to presence of aggressive underlying malignancy such as metastatic melanoma and lung cancer. These patients may succumb to their underlying malignancy in a short period of time; uptake in the prostate has no clinical relevance as patients with low risk (Gleason lower than 6) can survive up to 16 years and with high risk prostate cancer (Gleason higher than 7) can survive up to 6 years [18]. However, patients with high Gleason score do require aggressive therapy [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients that were excluded from the study and did have persistent uptake did not have biopsy nor had their serum PSA evaluated due to presence of aggressive underlying malignancy such as metastatic melanoma and lung cancer. These patients may succumb to their underlying malignancy in a short period of time; uptake in the prostate has no clinical relevance as patients with low risk (Gleason lower than 6) can survive up to 16 years and with high risk prostate cancer (Gleason higher than 7) can survive up to 6 years [18]. However, patients with high Gleason score do require aggressive therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, no matter what type of uptake is seen in patients who have nonaggressive underlying malignancies, this finding should be further evaluated, as incidentally found prostate cancers can also cause mortality in this once thought nonlethal disease [19, 20] and the treatment may be based on the grade, stage, and the age of the patient [18, 21]. Studies have shown survival benefit in patients who have incidental prostate cancers resected during cystoprostatectomy for bladder cancer [22] and such studies need to be performed in the setting of other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental Prostatic carcinoma (IPCa) is defined as a "cancer which lacks apparent neoplastic symptoms or cancer which is unusually detected by microscopic examination of resected tissue that had been previously diagnosed as benign. 11 Different screening programs in the past have led to detection of prostate carcinoma but, With the use of traditional and latest modern screening methods and techniques for PAC, including digital rectal examination (DRE), measurement of prostate-specific antigen (PSA), and transrectal ultrasound (TURS) and prostate biopsy, have not only reported better diagnosis of PAC but also an increase in the incidence of PAC. 12 Today, PCa is more frequently being diagnosed in asymptomatic patients with localized disease.…”
Section: Disscusionmentioning
confidence: 99%
“…Incidental PCa (IPCa) is defined as a “cancer which lacks apparent neoplastic symptoms or cancer which is unusually detected by microscopic examination of resected tissue that had been previously diagnosed as benign.” 9 Today, PCa is more frequently being diagnosed in asymptomatic patients with localized disease. Owing to early diagnosis, more cases of focal PCa or IPCa are diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to early diagnosis, more cases of focal PCa or IPCa are diagnosed. 9 , 10 There is also a population group composed of patients with obstructive lower urinary tract symptoms (LUTS) that are probably an outcome of BPH. These patients do not manifest with clinical symptoms nor does the disease show up on digital rectal examination (DRE), and they often have normal PSA levels.…”
Section: Introductionmentioning
confidence: 99%